Perineal Hernia in Dogs: Which Technique Should We Use? - Sprada, Arícia Gomes; Huppes, Rafael Ricardo; Feranti, João Pedro Scussel; de Souza, Fernando Wiecheteck; Coelho, Lívia de Paula; Moraes, Paola Castro; Minto, Bruno Watanabe (Acta Scientiae Veterinariae, 2017)
Background: Perineal hernia may be unilateral or bilateral and results from weakening and separation of the pelvic diaphragm muscles, favoring the abdominal viscera herniation into the perineal subcutaneous. The factors described as possible etiology of this affection are prostate hyperplasia, senile muscular atrophy, myopathy and hormonal imbalances. Several herniorrhaphy techniques are available in literature presenting different rates of success leaving the question whether there is any technique that is predominantly better than others are. This case report aims to describe five cases of perineal hernia treated with four different techniques performed by four experienced surgeons. Cases: Case 1. Semitendinous muscle transposition: A 8-year-old intact male Shitzu (6 kg) was referred for the evaluation of a swelling in the right perineal region. The mass was soft and regressed into de pelvic cavity during palpation. Abdominal ultrasound and radiography were taken, which reveled perineal hernia and a mild prostate enlargement. The patient was prepared for hernia repair with semitendinous muscle transposition and orchiectomy. Case 2. Internal obturator muscle transposition: A 9-year-old intact male mixed breed dog (18kg) presenting a two-week long unilateral (right-side) perineral hernia. Ultrasound exam revealed a cystic prostate and adipose tissue as the hernia content. After clinical and image examination the patient was submitted to surgical repair using the internal obturator muscle transposition technique and orchiectomy. Case 3. Internal obturator muscle transposition associated to correction of rectal sacculation: A 12-year-old intact male mixed breed presenting swelling on the right side of the perianal region. The owner reported a 4-day long aquesia, emesis and increased volume in perineum for 6 months. During the rectal palpation, resected fecal content was present and rectal sacculation was suspected. Enema, simple abdominal radiography, contrast radiography and ultrasonography were performed. The exams showed perineal hernia with bowel content and presence of rectal sacculation. The patient was submitted to surgery in order to correct the perineal hernia and rectal sacculation, and to performe orchiectomy. Case 4. Polypropylene mesh: A 13-year-old intact male dachshund dog (8.6 kg) was referred to clinical examination due to a 1-year-history complaint of a mass in the right perineal area. The owner also reported rectal prolapse and stranguria noted two days prior the consultation. Ultrasound and radiography showed bladder, prostate and bowel contained in hernia sac. The patient underwent to hernia repair with polypropylene mesh and castration. Case 5. Bovine pericardium preserved in 4% formaldehyde: A 7-year-old intact male mixed breed dog (14 kg) was presented to clinical evaluation with swelling lateral to the anus and dyschezia. Abdominal radiography and ultrasound revealed images suggestive of perineal hernia with urinary bladder, prostate and bowl content. The patient was referred to surgery. Discussion: Perineal herniations are commonly related to weakness of pelvic diaphragm muscles. However, the etiology involved in this process is undetermined. Success rate of perineal hernia repair techniques vary in literature. It can be speculated that local factors may influence these results, such as the surgeon ability to perform the technique or to recognize components that adversely affects the surgery. The results were considered satisfactory in all cases, which may answer the question: the better technique is the one we perform better.